GLYCINE betaine and seaweed-based biostimulants improved leaf water status and enhanced photosynthetic activity in sweet cherry trees - Afonso, Sílvia; Oliveira, Ivo; Guedes, Francisco; Meyer, Anne S.; Gonçalves, Berta (Frontiers in Plant Science, 2024)
Sweet cherry is a high-value crop, and strategies to enhance production and sustainability are at the forefront of research linked to this crop. The improvement of plant status is key to achieving optimum yield. Biostimulants, such as glycine betaine (GB) or seaweed-based biostimulants (e.g. Ecklonia maxima (EM)), can represent a sustainable approach to improving plant conditions, even under adverse environmental circumstances. Despite their potential, few studies have focused on the effects of GB or EM exogenous application on sweet cherry tree physiology. To address this lack of research, a study was conducted in a Portuguese sweet cherry commercial orchard, using Lapins and Early Bigi cultivars. Trees were treated with products based on GB and EM at two different concentrations (GB 0.25 %(v/v) and GB 0.40 % (v/v); EM 0.30 % (v/v) and EM 0.15 % (v/v)), a combination of the lowest concentrations of both biostimulants (Mix -GB 0.25 % and EM 0.15 %), and a control group (C) treated with water. Applications were performed over three consecutive years (2019, 2020 and 2021) at three different phenological stages, according to the BBCH scale: 77, 81, and 86 BBCH. Results showed, in general, that the application of biostimulants led to improvements in water status as well as significantly lower values of electrolyte leakage and thiobarbituric acid reactive substances compared to C samples. Additionally, biostimulants reduced pigment loss in the leaves and enhanced their biosynthesis. The Chlorophylla/Chlorophyllb ratio, ranging from 2 to 4, indicated a greater capacity for light absorption and lower stress levels in treated leaves. Soluble sugar and starch content decreased during fruit development in both cultivars and years, however, biostimulants increased these contents, with increments of approximately 15% to 30% in leaves treated with EM. Soluble protein content also showed the same pattern for treated leaves. Biostimulants, especially EM, demonstrated a significant positive effect (P ≤ 0.001) on total phenolic content, with increases of approximately 25% to 50% in treated leaves. In conclusion, the application of biostimulants, especially algae-based, significantly improved tree performance by enhancing physiological parameters and stress resilience and could represent a novel approach in fruit production systems.